Experimental study on the effect of tool life during the machining of Nimonic C-263 alloy using cryogenic coolant - Roslim, Muhammad Ikhwan (2024)
Nimonic C-263, a nickel-based alloy, has gained prominence in aerospace and high-temperature applications due to its exceptional properties. However, its low thermal conductivity poses challenges during machining, leading to rapid tool wear and reduced tool life. Traditional flood lubrication methods have been insufficient in addressing these issues. The difficulty in machining Nimonic C-263 alloy arises from the extreme heat generated due to its low thermal conductivity, impacting tool wear and fatigue life. Conventional flood lubrication methods have proven inadequate in mitigating the challenges posed by machining this alloy. This research focuses on evaluating the impact of cutting parameters on tool life during turning of Nimonic C-263 superalloy using cryogenic coolant, specifically Carbon dioxide (CO2) gas. A Physical Vapor Deposition (PVD) cemented carbide insert is employed as the cutting tool on a Computer Numerical Control (CNC) Haas ST-20 lathe machine. Response Surface Methodology (RSM) is utilized to design experiments that investigate the influence of feed rate, cutting speed, and depth of cut on the longevity of coated carbide inserts. The tool life calculation was based on tool wear progression and the cumulative tool travels per minutes. The study reveals that cutting speed significantly influences tool life, followed by feed rate and depth of cut according to Analysis of Variance (ANOVA). The experiment demonstrates that the Physical Vapor Deposition (PVD) coated carbide insert exhibits a maximum tool life of 26.81 minutes and a minimum of 3.56 minutes. The developed mathematical model validated as the percentage error 8.08%. 61 mm/s of cutting speed, 0.15 m/rev of feed rate and 0.5 mm of depth of cut are the optimum parameter of the cryogenic cooling machining of Nimonic C-263. Flank wear and fracture wear are identified as primary tool failure mode affecting cutting tools, with abrasion and diffusion being tool wear mechanisms observed.